Shock-induced transformation of non-magnetic to magnetic ISM dust analogue. Issue 4 (20th September 2022) - Roy, Arijit; Singh, Surendra V; Meka, J K; Ramachandran, R; Sahu, D; Gautam, A; Vijay, T; Vishakantaiah, Jayaram; Janardhan, P; Rajasekhar, B N; Bhardwaj, Anil; Mason, N J; et al.
ABSTRACT: The fate of organometallic dust subjected to extreme conditions, especially the shock fronts, in the interstellar medium (ISM) has not been explored to date. Iron and cyclopentadiene, which have been found to be present in the ISM, are known to react and produce the organometallic compound ferrocene under terrestrial conditions. In our experiment we subjected ferrocene, a possible proxy of such dust, to ∼5.6 Mach (M) shock commensurate with conditions encountered in the ISM, leading to a temperature rise up to 7300 K within 2 ms. Analysis of the post-shock residue showed the presence of a α-Fe and Fe3 C composite that responded to an external magnetic field. These results show that a non-magnetic dust composed of molecules containing transition metals undergoing shock processing in the ISM can dissociate and synthesize dust that is then magnetic. Such drastic transformations from non-magnetic to magnetic dust induced by shocks might be of importance in interstellar polarization.